2021
DOI: 10.1186/s12872-021-02273-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex and age difference in risk factor distribution, trend, and long-term outcome of patients undergoing isolated coronary artery bypass graft surgery

Abstract: Background Preoperative coronary artery disease risk factors (CADRFs) distribution and pattern may also have an important role in determining major adverse cardiovascular events (MACEs). In this study, we aimed to evaluate the CADRFs distribution and trend over 10 years and also the long-term outcome of CABG in different age-sex categories. Method In this registry-based serial cross-sectional study, we enrolled 24,328 patients who underwent isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…The importance of EF on CABG survival has also been repeatedly reported in other studies ( 28 , 29 ), some of which revealed a dose-response relationship between decreasing EF and overall risk of death ( 28 ). This is also the case with the role of our other selected features in estimating long-term CABG survival, including age ( 30 , 31 ), glucose and lipid profile ( 32 – 35 ), Hb ( 36 , 37 ), Cr ( 38 , 39 ), and BMI ( 31 ).…”
Section: Discussionmentioning
confidence: 86%
“…The importance of EF on CABG survival has also been repeatedly reported in other studies ( 28 , 29 ), some of which revealed a dose-response relationship between decreasing EF and overall risk of death ( 28 ). This is also the case with the role of our other selected features in estimating long-term CABG survival, including age ( 30 , 31 ), glucose and lipid profile ( 32 – 35 ), Hb ( 36 , 37 ), Cr ( 38 , 39 ), and BMI ( 31 ).…”
Section: Discussionmentioning
confidence: 86%
“…In patients with stable CAD with conservative treatment, it has been shown that the absence of a decrease in CAVI after six months was associated with an unfavorable prognosis [ 36 ]. The traditional fight against risk factors (smoking, dyslipidemia, diabetes mellitus, arterial hypertension [ 2 ]) is manifested, among other things, by an improvement in the elasticity of the vascular wall, but it is not clear how pronounced this can be in patients after CABG; such studies have not been conducted. The question also remains open—is it possible to influence the long-term prognosis after CABG if it is possible to achieve a decrease in CAVI in the course of therapeutic and prophylactic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term results after coronary artery bypass grafting depend not only on the completeness of revascularization, on the initial severity of coronary and myocardial lesions, but also on comorbidity (diabetes mellitus, arterial hypertension, diseases of the lungs, kidneys, etc.) [ 1 , 2 ]. In addition, of importance is the state of the vascular system as a whole, which can also affect the course of the disease after coronary artery bypass grafting (CABG).…”
Section: Introductionmentioning
confidence: 99%
“…The results are similar to those of some previous studies [ 7 9 ]. It has been suggested that females have a higher risk of adverse cardiovascular events and death after CABG [ 10 , 11 ]. However, gender was not a confounding factor during the data analysis of this study.…”
Section: Discussionmentioning
confidence: 99%